2017
DOI: 10.1177/0964663916679039
|View full text |Cite
|
Sign up to set email alerts
|

Remorse in Context(s)

Abstract: The presence or absence of ‘signs of remorse’ is often understood to have consequences for judges’ sentencing decisions. However, these findings raise the questions, first, how ‘remorse’ is communicated and demonstrated by defendants within court settings, and second, whether remorse plays a uniform role across and between various offence and offender types. Drawing on ethnographic data gathered in a Dutch criminal court, we contextualize remorse to answer these questions. First, we demonstrate that the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…While part of this research focuses on professionals’ management of emotions (Bergman Blix and Wettergren, 2018; Flower, 2019; Mack and Roach Anleu, 2005), other studies have described how legal professionals interpret lay people’s expressions and how, for example, one may evaluate defendants’ remorse in relation to questions of guilt and punishment (e.g. Bandes, 2014; Johansen, 2019; Tata, 2010, 2020; van Oorschot et al, 2017). Defendants’ emotional reactions have thus been subject to extensive research interest; however, victims’ emotions and the impact they have on legal professionals remain less well-explored, just as differences between the roles of the police and courtroom actors are seldom explored within the same research projects on victims (for exceptions, see Shapland et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…While part of this research focuses on professionals’ management of emotions (Bergman Blix and Wettergren, 2018; Flower, 2019; Mack and Roach Anleu, 2005), other studies have described how legal professionals interpret lay people’s expressions and how, for example, one may evaluate defendants’ remorse in relation to questions of guilt and punishment (e.g. Bandes, 2014; Johansen, 2019; Tata, 2010, 2020; van Oorschot et al, 2017). Defendants’ emotional reactions have thus been subject to extensive research interest; however, victims’ emotions and the impact they have on legal professionals remain less well-explored, just as differences between the roles of the police and courtroom actors are seldom explored within the same research projects on victims (for exceptions, see Shapland et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In this author's view, the humanisation process affirms the fairness of the system for the professionals more so than for the individual defendants, and Tata links this in with why the criminal justice system is so ineffective in reducing offending, and particularly talented in ‘recycling its clientele’ (p.9). He cites (p.105) Van Oorschot, Manscini & Weenink (2017) where they describe the anger professionals can feel in court where a defendant displays insouciance, with court actors noting a defendant ‘was just sitting there’. If it appears that the defendant regards the system with contempt, then the legitimacy of the court comes into question more so.…”
mentioning
confidence: 99%
“…In South Carolina, for example, remorse was the third most aggravating factor in capital cases (Zhong, 2015). van Oorschot, Mascini, and Weenink (2017) refer to the absolute centrality of remorse to judges' decision-making in Dutch courts. In England, an observational study of 52 sentencers, sentencing 162 defendants between them, found that, while judges took account of the immediate circumstances of the offence, the defendant's response to the offence was important.…”
mentioning
confidence: 99%